Analysis role of zakat on reducing poverty and increasing the economic value in Wilayah Persekutuan Kuala Lumpur / Amir Hamzah Zulkifli. - Zulkifli, Amir Hamzah (2019)
Analysis role of zakat on reducing poverty and increasing the economic value in Wilayah Persekutuan Kuala Lumpur / Amir Hamzah Zulkifli.